Nature and culture for the ecotourism development in the Province of Concepción, Junín, Perú - Maldonado Oré, Edith Mercedes (2020)
Culture and nature are very important inputs for ecotourism, and these are precisely the resources the districts of Concepción, Matahuasi, Santa Rosa de Ocopa and Aco have. The identification of cultural and natural resources and the relationship of man with his environment was the objective of this research. The method used was the qualitative one; the technique, the interview, with a collection sheet of cultural and natural data as the instrument. With the resources identified in Matahuasi, there can be practiced hiking, landscape tourism, recreation, flora and fauna observation, agritourism, environmental education, experiential and gastronomic tourism. In Aco, there can be developed experiential tourism, agritourism and landscape tourism. In Santa Rosa de Ocopa, cultural tourism, agritourism, experiential tourism and hiking. In Concepción, cultural tourism, experiential tourism, agritourism and landscape tourism. Based on the potential of the 4 districts, an ecotourism circuit could be implemented, which would have as its head the city of Concepción, since this has the appropriate services for tourism. The project would improve the quality of life and economic sustainability of the population living in the above-mentioned districts.